Porosity Structure Offering Improved Biomechanical Stress Distribution and Enhanced Pain-Relieving Potential - Chia-Cheng Lin; Chia-Yu Wu; Mao-Suan Huang; Bai-Hung Huang; Hsin-Hua Chou; Keng-Liang Ou; Chung-Ming Liu; Fang-Tzu Pai; Han-Wei Huang; Pei-Wen Peng (Applied Sciences, 2020)
In this study, we developed a three-dimensional (3D) human body model and a body sculpting clothing (BSC) which was fitted onto that body to simulate the biomechanical stress variations of the BSC with different porosity structures using the finite element method. The mechanical properties of the BSC with different porosity structures were also examined through the tensile testing. Analytical results indicated that the Von Mises stress of the BSC with a porosity structure of 10.28% varied from 0.076 MPa to 337.79 MPa. As compared with a porosity structure of 35.18%, the von Mises stress varied from 0.067 MPa to 207.30 MPa. The von Mises stress decreased as the porosity increasing. Based on the statistical analysis findings, we obtained a formula to predict the biomechanical relationships (von Mises stress and strain) between the human body and porosity of the BSC. Therefore, these findings could offer potential information in the modification of BSC for pain-relieving applications.